2016
DOI: 10.1097/fjc.0000000000000367
|View full text |Cite
|
Sign up to set email alerts
|

Helix B Surface Peptide Protects Cardiomyocytes Against Hypoxia/Reoxygenation-induced Apoptosis Through Mitochondrial Pathways

Abstract: These results indicated that HBSP has protective effects against H/R-induced apoptosis by regulating the mitochondrial pathway. This mechanism involves inhibiting mitochondrial ROS generation, inhibiting caspase-3 activity, reducing ΔΨm collapse, reducing cytochrome release, and balancing anti and proapoptotic Bcl-2 family proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Recent research shows that Bcl-2 protein, a key member of the Bcl-2 family, plays a central role in the survival of vascular endothelial cells by maintaining mitochondrial membrane potential and suppressing mitochondria-dependent apoptosis under ischemic conditions. Multiple studies131545 have suggested that downregulation of mitochondrial Bcl-2 destabilises the integrity of the mitochondrial outer membrane and enhances the release of cytochrome c from mitochondria, leading to activation of the caspase-mediated apoptosis pathway. In the present study, we observed that TDB markedly protected vascular endothelial cells against ischemic damage through increasing mitochondrial Bcl-2 protein expression and maintaining mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research shows that Bcl-2 protein, a key member of the Bcl-2 family, plays a central role in the survival of vascular endothelial cells by maintaining mitochondrial membrane potential and suppressing mitochondria-dependent apoptosis under ischemic conditions. Multiple studies131545 have suggested that downregulation of mitochondrial Bcl-2 destabilises the integrity of the mitochondrial outer membrane and enhances the release of cytochrome c from mitochondria, leading to activation of the caspase-mediated apoptosis pathway. In the present study, we observed that TDB markedly protected vascular endothelial cells against ischemic damage through increasing mitochondrial Bcl-2 protein expression and maintaining mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies13141516 have revealed that activation of anti-apoptotic Bcl-2 protein or inactivation of pro-apoptotic Bax protein could disturb the process of vascular endothelial cell apoptosis under ischemic conditions. In this study, we found that TDB significantly increased Bcl-2 protein expression in a dose-dependent manner without affecting Bax expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H/R induced intracellular and mitochondrial ROS accumulation; however, whether the observed increase in mitochondrial ROS levels was amplified by intracellular ROS accumulation, as has been previously reported, was not investigated in the present study (21,22). Although H/R-induced intracellular ROS accumulation directly interacts with mitochondrial proteins and lipids to accelerate mitochondrial dysfunction (23), in the present study, scavengers of intracellular and mitochondrial ROS decreased the rate of apoptosis following H/R, suggesting that mitochondrial ROS directly induced apoptosis. A decrease in the percentage of Annexin V + /PIand Annexin V + /PI + cells following treatment with GA in H/R-induced cells was also observed, which suggested that necrosis had also occurred; however, the effects of GA on necrosis require further investigation.…”
Section: Discussionmentioning
confidence: 50%
“…RSV sensitized colorectal [118] and breast [119] cancer cells to DO x via facilitating apoptosis and enhancing intracellular entrapment of DO x and through inhibiting breast cancer cells proliferation and invasion, respectively. DO x -induced either injuries [120] or apoptosis [121] H9c2 cardiac cells were protected by RSV via sirtuin 1 (SIRT1) activation and the AMPK/P53 pathway, respectively.…”
Section: Do X and Rsvmentioning
confidence: 99%